Optimising the dose of static stretching to improve flexibility: a systematic review, meta-analysis and multivariate meta-regression - Ingram, L. A.; Tomkinson, G. R.; d`Unienville, N. M. A.; Gower, B.; Gleadhill, S.; Boyle, T.; Bennett, H. (Sports Medicine, 2025)
Background: Static stretching is widely used to increase flexibility. However, there is no consensus regarding the optimal dosage parameters for increasing flexibility. Objectives: We aimed to determine the optimal frequency, intensity and volume to maximise flexibility through static stretching, and to investigate whether this is moderated by muscle group, age, sex, training status and baseline level of flexibility. Methods: Seven databases (CINAHL Complete, Cochrane CENTRAL, Embase, Emcare, MEDLINE, Scopus, and SPORTDiscus) were systematically searched up to June 2024. Randomised and non-randomised controlled trials investigating the effects of a single session (acute) or multiple sessions (chronic) of static stretching on one or more flexibility outcomes (compared to non-stretching passive controls) among adults (aged = 18 years) were included. A multi-level meta-analysis examined the effect of acute and chronic static stretching on flexibility outcomes, while multivariate meta-regression was used to determine the volume at which increases in flexibility were maximised. Results: Data from 189 studies representing 6654 adults (61% male; mean [standard deviation] age = 26.8 ± 11.4 years) were included. We found a moderate positive effect of acute static stretching on flexibility (summary Hedges` g = 0.63, 95% confidence interval 0.52-0.75, p < 0.001) and a large positive effect of chronic static stretching on flexibility (summary Hedges` g = 0.96, 95% confidence interval 0.84-1.09, p < 0.001). Neither effect was moderated by stretching intensity, age, sex or training status, or weekly session frequency and intervention length (chronic static stretching only) [p > 0.05]. However, larger improvements were found for adults with poor baseline flexibility compared with adults with average baseline flexibility (p = 0.01). Furthermore, larger improvements in flexibility were found in the hamstrings compared with the spine following acute static stretching (p = 0.04). Improvements in flexibility were maximised by a cumulative stretching volume of 4 min per session (acute) and 10 min per week (chronic). Conclusions: Static stretching improves flexibility in adults, with no additional benefit observed beyond 4 min per session or 10 min per week. Although intensity, frequency, age, sex and training status do not influence improvements in flexibility, lower flexibility levels are associated with greater improvement following both acute and chronic static stretching. These guidelines for static stretching can be used by coaches and therapists to improve flexibility.